Gerenciamento dos resíduos de serviços de saúde da Unidade de Terapia Intensiva do Pronto Socorro do Hospital das Clínicas da Faculdade de Medicina de Botucatu – UNESP - Araujo, Priscila de Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Health care waste (HCW) is the type of waste that results from activities performed in health care services during care provision to humans or animals. Presently, according to RDC 306/04, issued in 2004 by Anvisa, and Resolution no. 358/05, by CONAMA, waste groups have the following classification: Group A (biological waste), Group B (chemical waste), Group C (waste containing radionucleotides), Group D (common waste) and Group E (piercing and cutting waste). In Brazil, 149 tons of wastes are collected every day, and HCW corresponds to approximately 1% to 3 % of that total. An efficient way to adequately manage HCW is through the Health Care Waste Management Plan (HCWMP), and it is possible to reduce the risk posed by certain materials in addition to ensuring disposal in an ecologically correct and economical fashion. According to the Pan-American Health Organization (PAHO), the management process enables health care establishments to adequately manage waste. Hence, there is greater control and reduction in the health risks caused by infectious or special waste, in addition to facilitated recycling, treatment, storage, transport and final disposal of solid hospital waste in an environmentally safe fashion. To evaluate the management of HCW of Groups A and D from the Intensive Care Unit of the University Emergency Hospital - FMB - UNESP in the city of Botucatu according to the guidelines presently in force. The waste flow was followed up, and during four random days in the month of September 2011, waste was quantified by estimating daily and monthly values, according to its classification. : In 2011, the University hospital has produced an average of 57,676.8 kg/month of biological and common waste. By adding Groups A and D, during the four days, approximately 209.8 Kg of waste (202.2 Kg of Group A and 7.6 Kg of Group D) were produced in the establishment under study, which... (Complete abstract click electronic access below)

Resíduos de Serviço de Saúde (RSS) são aqueles que resultam de atividades exercidas nos serviços que têm relação com o atendimento à saúde seja humana ou animal. Atualmente, de acordo com a RDC 306/04 de 2004 da Anvisa e a Resolução n° 358/05 do CONAMA, os grupos possuem a seguinte classificação Grupo A (resíduo biológico), Grupo B (resíduo químico), Grupo C (resíduo que contenha radionucleotídeo),Grupo D (resíduo comum) e Grupo E (resíduo perfurocortante). No Brasil, são coletadas diariamente 149 mil toneladas de lixo por dia sendo que os resíduos de serviços de saúde (RSS) correspondem a cerca de 1% a 3 % deste total. Um modo eficiente de manejar adequadamente os RSS é através do Plano de Gerenciamento dos Resíduos de Serviços de Saúde (PGRSS), sendo possível reduzir os riscos que alguns materiais acarretam, além de garantir descarte de forma ecologicamente correta e econômica. Segundo a Organização Pan-Americana de Saúde (Opas), o processo de gerenciamento permite às instituições que prestam serviços a saúde um manejo adequado dos resíduos. Com isso, tem-se um maior controle e redução dos riscos para a saúde, ocasionados pelos resíduos infecciosos ou especiais, além de facilitar a reciclagem, o tratamento, o armazenamento, o transporte e a disposição final dos resíduos sólidos hospitalares de forma ambientalmente segura. Avaliar o gerenciamento dos RSS dos grupos A e D da Unidade de Terapia Intensiva do Pronto Socorro do HC –FMB- UNESP da cidade de Botucatu de acordo com as normas vigentes. : Foi realizado o acompanhamento do fluxo de resíduos e durante quatro dias aleatórios do mês de setembro de 2011 foi realizada a quantificação desses resíduos estimando um valor diário e mensal, de acordo com sua classificação. O HC vem produzindo no ano de 2011 uma média de 57.676,8 kg/mês de resíduo biológico e comum... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Saúde – Administração; Exposição a agentes biológicos; Hospitais – Eliminação de resíduos